2005
DOI: 10.2337/diacare.28.9.2261
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ACE Inhibitors or Angiotensin II Type 1 Receptor Blockers on the Development of New-Onset Type 2 Diabetes

Abstract: OBJECTIVE -Angiotensin II has been shown to increase hepatic glucose production and decrease insulin sensitivity. Patients who utilize either an ACE inhibitor (ACEI) or angiotensin receptor blocker (ARB) may experience a decreased incidence of new-onset type 2 diabetes. RESEARCH DESIGN AND METHODS-Three reviewers conducted a systematic literature search of Medline, EMBASE, CINAHL, and the Cochrane Library (1966 to present) to extract a consensus of trial data involving an ACEI or ARB with an end point of new-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(139 citation statements)
references
References 22 publications
6
133
0
Order By: Relevance
“…In a recent meta-analysis of the randomized, controlled, clinical trials using ACEI or ARB to prevent new-onset type 2 diabetes as a primary or secondary end point, it was concluded that ACEI and ARB have a significant ability to reduce the occurrence of new-onset type 2 diabetes among patients with hypertension, coronary artery disease, and heart failure (39).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis of the randomized, controlled, clinical trials using ACEI or ARB to prevent new-onset type 2 diabetes as a primary or secondary end point, it was concluded that ACEI and ARB have a significant ability to reduce the occurrence of new-onset type 2 diabetes among patients with hypertension, coronary artery disease, and heart failure (39).…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] In addition, some studies suggest a beneficial influence of RAAS blockade on insulin resistance and glucose homeostasis. 31,34 Possible mechanisms responsible for the reduced incidence of diabetes in these trials include improvement in insulin mediated glucose uptake, enhanced endothelial function, increased nitric oxide activation, reduced inflammatory response, and increased bradykinin levels.…”
Section: Raas Inhibition In the Clinical Settingmentioning
confidence: 99%
“…[31][32][33] In addition, some studies suggest a beneficial influence of RAAS blockade on insulin resistance and glucose homeostasis. 31,34 Possible mechanisms responsible for the reduced incidence of diabetes in these trials include improvement in insulin mediated glucose uptake, enhanced endothelial function, increased nitric oxide activation, reduced inflammatory response, and increased bradykinin levels. 35 On the other hand, it has been established that MR antagonism favourably affects cardiovascular outcomes in the clinical setting, as has been established in the RALES (Randomized Aldactone Evaluation Study) and EPHESUS (Eplerenone Post-Acute Myocardial Infarction Heart Failure Efficacy and Survival Study) trials.…”
Section: Raas Inhibition In the Clinical Settingmentioning
confidence: 99%
“…Routine ACE inhibition in patients with diabetes before albuminuria may prevent nephropathy and be cost-effective/saving (62,63). More widespread use of ACE inhibition in the general hypertensive population over the longer run actually may prevent or at least delay new-onset diabetes (64). Younger black individuals who currently have low-normal GFR (60 to 80 ml/min per 1.73 m 2 ) especially with genetic/family risk and are identified through high-yield screening approaches may be critical to improving outcomes in this population (65).…”
Section: Failure Of Therapy and Future Of Ckdmentioning
confidence: 99%